Design and Development of 72.83 MHz Signal Booster Transmitter to increase the remote control coverage - Catur Budi Waluyo (Institut Teknologi Dirgantara Adisutjipto, 2018)
In the development of wireless communication, the development of Unmanned Aerial Vehicle a long distance is a challenge. One technique to make it happen is by using a signal amplifier that can add facilities to the Unmanned Aerial Vehicle controller using Remote Control (RC).The signal amplifier that operates at 72.83 MHz frequency is designed with four amplifier levels with 2SC930, 2SC2053 and 2SC1971 series transistors. This signal amplifier is designed to operate in class A for levels I, II, III, and class C for level IV with impedance adjustment circuits namely type T and L. On the part of the omnidirectional transmitter antenna. According to the designer, the frequency used is 72.83MHz with a bandwidth of 30kHz. The amplitudo peak level produced is -27dBm with a reference level of 0 dBm. High results indicate the amplifier can work at a frequency of 72.83 MHz with power ranging from 4.5 watts or gain of 16.58 dB and approaching the designer's results. Voltage Standing Wave Ratio (VSWR) which measures 1.1 with a minimum VSWR limit of 1.